Current elephant range and status in Mozambique - Chambal, Mateus (Pachyderm, 1993)
Provides a general overview of the range and status of the African elephant in Mozambique. There are three main populations; central, northern and southern, in order of the most promising in the long term. The need to create conservation zones in areas with significant elephant populations and proper planning for human settlements are some of the issues discussed in order to avoid human/animal conflict.